Ultralow Frequency Electrodynamics of Magnetosphere‐Ionosphere Interactions Near the Plasmapause During Substorms. Issue 9 (13th September 2018) - Streltsov, Anatoly V.; Mishin, Evgeny V.
Abstract: Ultra low frequency (ULF) electromagnetic waves have been regularly observed by the CRRES, Cluster, and Van Allen Probes satellites near the plasmapause during substorms. Frequently, the small‐scale waves are detected together with a large‐scale quasi‐stationary electric field collocating with mesoscale plasma flows penetrating into the plasmasphere. These observations suggest that the plasmapause plays an important role in the conversion of the kinetic energy of energetic particles moving toward the Earth from the reconnection site in the magnetotail into a large‐scale electric field. The field penetrates along the magnetic field into the ionosphere and generates small‐scale, shear Alfvén waves and field‐aligned currents. These waves can form a standing pattern between the hemispheres, and under certain conditions, they can be amplified by interactions with the ionosphere. This scenario is verified in the paper by reproducing with simulations structure and amplitude of the ULF waves observed by the Van Allen Probe‐A satellite near the plasmapause on 17 March 2015. The simulations are based on the reduced two‐fluid MHD model describing generation of ULF Alfvén waves and field‐aligned currents by the ionospheric feedback instability driven by the large‐scale electric field. Simulations demonstrate good, quantitative agreement between spatial structure, frequency, and amplitude of the simulated waves and the observations. Key Points: We explain large‐scale and small‐scale electric fields observed near the plasmapause Simulations reveal that the small‐scale fields are produced by the ionospheric feedback mechanism We identify ionospheric parameters promoting development of the small‐scale structures